If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 6x + -8 Reorder the terms: -20 + 3x = 6x + -8 Reorder the terms: -20 + 3x = -8 + 6x Solving -20 + 3x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -20 + 3x + -6x = -8 + 6x + -6x Combine like terms: 3x + -6x = -3x -20 + -3x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -20 + -3x = -8 + 0 -20 + -3x = -8 Add '20' to each side of the equation. -20 + 20 + -3x = -8 + 20 Combine like terms: -20 + 20 = 0 0 + -3x = -8 + 20 -3x = -8 + 20 Combine like terms: -8 + 20 = 12 -3x = 12 Divide each side by '-3'. x = -4 Simplifying x = -4
| 10+3y=-6 | | S=Ngj | | 3(2+x)=-36 | | x^2-2400=0 | | -2g-6=-9 | | 360=(6+3w)(w) | | 18+0.5x=25 | | 3(2c-5)+2c= | | -8w-2=-10-4w | | 4x+6-x=22+6 | | -1/3(9s-36t=-5)= | | 24+2X=110 | | -5+3y=-6 | | 5p-2q=3m+d | | -7(x+2y+5z)= | | 11a+b=5a+24 | | 8y=-8+7y | | -10+3y=-6 | | 64-x=156 | | y+1=16-2y+6 | | 5x-3=13+2x | | 10/75=18/n | | -2y+18=4(y+3) | | (K^1/10)^-2/(k^9)^1/5 | | 55=4(2y-3) | | P=20log(146*2300) | | 1-2j=10-3j | | 5(y+8)-8y=25 | | -6=-5/6v | | 8x+2x-3y-9x= | | -2w-3(3x+4w)+2x= | | 2(v-5)-5v=-28 |